Contribution of image processing for analyzing the cellular structure of cork. (27th December 2017) - Lagorce‐Tachon, Aurélie; Mairesse, Fabrice; Karbowiak, Thomas; Gougeon, Régis D.; Bellat, Jean‐Pierre; Sliwa, Tadeusz; Simon, Jean‐Marc
Abstract: The alveolar structure of cork confers to this natural material specific physical properties such as low permeability to liquids and gases, advanced thermal and acoustic insulation, and high elasticity. In this paper, a morphological analysis of natural cork cells is presented including statistical distributions of structural quantities. These results were obtained from the study of scanning electron microscopy images of natural cork stoppers. After automation of the image processing analysis, the area and perimeter distributions were measured in different cork sections: axial, tangential, and radial. Perpendicular to the radial direction we also focused on growth rings, which are characterized by smaller cell sizes. This systematic image analysis offers new possibilities to investigate the material at the cell scale and provides useful statistical information about the cork structure. Abstract : An automatic morphological analysis of natural cork cells is presented including statistical distributions of structural quantities (area, perimeter). These results were obtained from the study of scanning electronic microscopy images of natural cork stoppers. In the axial section we could identify the growth ring with smaller alveoli.